THEORETICAL AND PRACTICAL BASES FOR TEACHING SIGHT TRANSLATION (Journal of Foreign Language Studies, 2021)
This paper analyzes the important role of sight translation in translation and interpreting undergraduate programmes, describes its expected outcomes and proposes activities to be carried out in a course. The main goals of this paper are to provide learners with essential techniques of sight translation and to increase their interests in learning translation and interpreting.
Keywords: interpreting; sight translation; teaching interpreting